Pengaruh Program Keluarga Harapan (PKH), Bantuan Sembako, dan BLT Kesra terhadap Ketahanan Anggaran Rumah Tangga Miskin di Kecamatan Sumbawa - Rabiatul Adawiyah; Arya Zulfikar Akbar (SENTRI: Jurnal Riset Ilmiah, 2026)
Poverty alleviation at the regional level remains a structural challenge necessitating comprehensive social protection. This study investigates the impact of the Family Hope Program (PKH), Non-Cash Food Assistance (Sembako), and the localized Direct Cash Assistance (BLT Kesra) on the household budget resilience of impoverished communities in Sumbawa District. Employing a quantitative descriptive-associative design, primary data were collected through purposive sampling from 96 active beneficiary families. The empirical data were rigorously analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The structural model evaluation reveals a coefficient of determination ($R^2$) of 0.491, indicating that the simultaneous integration of these three social assistance programs explains 49.1% of the variance in household budget resilience. Partially, all three variables exhibit a positive and statistically significant effect. PKH emerges as the most dominant determinant, functioning as the primary liquidity anchor for mandatory expenses. Furthermore, Sembako ensures food inventory resilience, while BLT Kesra provides crucial quick cash for short-term solvency. Viewed through a public sector accounting lens, the synchronized distribution of these conditional and unconditional transfers, supported by transparent digital systems like SIKS-NG, acts as a critical buffer against economic shocks and prevents the liquidation of essential domestic assets. Conclusively, synergizing targeted social safety nets with enhanced financial literacy is imperative for sustainable household economic stability.